Unstimulated apheresis for chimeric antigen receptor manufacturing in pediatric/adolescent acute lymphoblastic leukemia patients. Issue 5 (4th August 2020) - Jarisch, Andrea; Rettinger, Eva; Sörensen, Jan; Klingebiel, Thomas; Schäfer, Richard; Seifried, Erhard; Bader, Peter; Bonig, Halvard
Abstract: Autologous unstimulated leukapheresis product serves as starting material for a variety of innovative cell therapy products, including chimeric antigen receptor (CAR)‐modified T‐cells. Although it may be reasonable to assume feasibility and efficiency of apheresis for CAR‐T cell manufacture, several idiosyncrasies of these patients warrant their separate analysis: target cells (mononuclear cells [MNC] and T‐cells) are relatively few which may instruct the selection of apheresis technology, low body weight, and, hence, low total blood volume (TBV) can restrict process and product volume, and patients may be in compromised health. We here report outcome data from 46 consecutive leukaphereses in 33 unique pediatric patients performed for the purpose of CD19‐CAR‐T‐cell manufacturing. Apheresis targets of 2×10 9 MNC/1×10 9 T‐cells were defined by marketing authorization holder specification. Patient weight was 8 to 84 kg; TBV was 0.6 to 5.1 L. Spectra Optia apheresis technology was used. For 23 patients, a single apheresis sufficed to generate enough cells and manufacture CAR‐T‐cells, the remainder required two aphereses to meet target dose and/or two apheresis series because of production failure. Aphereses were technically feasible and clinically tolerable without serious adverse effects. The median collection efficiencies for MNC and T‐cells were 53% and 56%, respectively. In summary, CAR apheresis in pediatric patients, including the very young, is feasible, safe and efficient, but the specified cell dose targets can be challenging in smaller children. Continuous monitoring of apheresis outcomes is advocated in order to maintain quality.